2007
DOI: 10.1111/j.1600-0714.2007.00514.x
|View full text |Cite
|
Sign up to set email alerts
|

The assessment of oral health‐related quality of life by factor analysis in patients with Behcet's disease and recurrent aphthous stomatitis

Abstract: The factor structure of OHIP-14 was found to be reliable and sensitive to clinical parameters and treatment modalities in active patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
56
0
10

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(72 citation statements)
references
References 27 publications
(46 reference statements)
6
56
0
10
Order By: Relevance
“…The consequences of major organ involvement can largely be eliminated by immunosuppressive medications in BD, whereas mucocutaneous symptoms, as a mild disease spectrum, can remain active under a mild antiinflammatory agent (frequently colchicine)-based protocol (22)(23)(24)(25). In this context, producing new disease-specific or organspecific outcome measures for use in the decision-making process can be helpful in patient management (22)(23)(24)(25)(26)(27)(28)(29). Productivity loss at work and/or in daily life and diseasespecific fears can be considered as outcome measures in cases of BD; however, there have been no data presented to date regarding this issue.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of major organ involvement can largely be eliminated by immunosuppressive medications in BD, whereas mucocutaneous symptoms, as a mild disease spectrum, can remain active under a mild antiinflammatory agent (frequently colchicine)-based protocol (22)(23)(24)(25). In this context, producing new disease-specific or organspecific outcome measures for use in the decision-making process can be helpful in patient management (22)(23)(24)(25)(26)(27)(28)(29). Productivity loss at work and/or in daily life and diseasespecific fears can be considered as outcome measures in cases of BD; however, there have been no data presented to date regarding this issue.…”
Section: Introductionmentioning
confidence: 99%
“…Çalışmamızda literatüre dayanılarak hastaların seboreik olmayan bölgelerindeki, foliküler yerleşim göstermeyen eritemli papül ve püstüller PPL olarak kabul edilmiştir 42 . Literatürde, BH'de PPL'nin yaşam kalitesine etkisi saptanmamıştır 11,13,18,43 . Ayrıca bazı çalışmalarda deri lezyonlarının birlikte ele alındığı, ENBL, PPL olarak ayrılmadığı dikkat çekmiştir 13,43 .…”
Section: Discussionunclassified
“…Literatürde, BH'de PPL'nin yaşam kalitesine etkisi saptanmamıştır 11,13,18,43 . Ayrıca bazı çalışmalarda deri lezyonlarının birlikte ele alındığı, ENBL, PPL olarak ayrılmadığı dikkat çekmiştir 13,43 . Çalışmamızda, PPL'nin hastaların boş zamanı değerlendirme, okul/iş hayatlarını olumsuz etkilediği, ağrı skorlarını arttırdığı ve fiziksel fonksiyonlarında ve emosyonel sorunlara bağlı kısıtlılığa sebep olduğu gösterilmiştir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Although the aetiopathogenesis of both BD and RAU have not yet been clarified, several mechanisims such as local trauma, nutritional deficiency, food hypersensitivity, genetics, infection, immunoglobulin, immune complexes and psychological stress have all been suggested as the causes of these diseases (6,7). Previous studies have suggested that psychological disturbances such as stress and anxiety could play a role in the onset, BD and RAU (7)(8)(9). A chronic disease such as BD may lead to temporary or permanent functional disabilities and may cause some psychiatric disorders (7).…”
Section: Introductionmentioning
confidence: 99%